2004
DOI: 10.1007/s00526-004-0285-6
|View full text |Cite
|
Sign up to set email alerts
|

The scalar curvature problem on the four dimensional half sphere

Abstract: In this paper, we consider the problem of prescribing the scalar curvature under minimal boundary conditions on the standard four dimensional half sphere. We provide an Euler-Hopf type criterion for a given function to be a scalar curvature for some metric conformal to the standard one. Our proof involves the study of critical points at infinity of the associated variational problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…critical point z of K 1 with (∂K/∂ν)(z) > 0 and critical point y of K. In this paper, we generalize the results of [10]. We cancel the assumption of [10] which is (∂K/∂ν) < 0 at each critical point of K 1 that is the function…”
Section: Ben Ayed R Ghoudi and K Ould Bouh Nodeamentioning
confidence: 79%
See 4 more Smart Citations
“…critical point z of K 1 with (∂K/∂ν)(z) > 0 and critical point y of K. In this paper, we generalize the results of [10]. We cancel the assumption of [10] which is (∂K/∂ν) < 0 at each critical point of K 1 that is the function…”
Section: Ben Ayed R Ghoudi and K Ould Bouh Nodeamentioning
confidence: 79%
“…The goal of our first result is the construction of some solutions (u ε ) of (P ε ) which blow up at two different points, one of them lies on the boundary and the other is an interior point. This result implies that there are more critical points at infinity than the authors found in [10]. Before stating the result, we need to introduce some notations.…”
Section: Ben Ayed R Ghoudi and K Ould Bouh Nodeamentioning
confidence: 95%
See 3 more Smart Citations